Deciphering the Function of lncRNA XIST/miR-329-3p/TMBIM6 Axis in the Proliferation of Non-Small Cell Lung Cancer - Cheng Li; Shuai Song; Yuge Wang; Danlin Zhu (Journal of Investigative Surgery)
Objective Non-small cell lung cancer (NSCLC) remains a major health concern due to its high incidence and mortality rates. This study aimed to investigate the role and underlying mechanism of the long non-coding X inactivation-specific transcript (lncRNA XIST)/microRNA-329-3p (miR-329-3p)/transmembrane BAX Inhibitor Motif-6 (TMBIM6) axis in the proliferation, migration, and invasion of NSCLC, and its potential as a therapeutic target.Methods The expression levels of XIST, miR-329-3p, and TMBIM6 in NSCLC tissues and cell lines were assessed using quantitative real-time PCR (qRT-PCR), and their correlations with clinicopathological characteristics were examined. Dual-luciferase reporter assays and RNA immunoprecipitation (RIP) were used to validate the binding interactions among XIST and miR-329-3p, and TMBIM6. The malignant phenotypes of NSCLC cells, including proliferation, migration, invasion, and apoptosis, were assessed using CCK-8, Transwell assays, and flow cytometry.Results Silencing XIST significantly suppressed the proliferation, migration, and invasion of NSCLC cells while promoting apoptosis. Mechanistically, XIST functioned as a competitive endogenous RNA (ceRNA), sponging miR-329-3p and thereby downregulating its expression. Overexpression of miR-329-3p counteracted the oncogenic effects of XIST in NSCLC cells. Additionally, miR-329-3p downregulated TMBIM6 expression, while TMBIM6 overexpression counteracted the tumor-suppressive effects of miR-329-3p.Conclusion Silencing XIST upregulates miR-329-3p, leading to the suppression of TMBIM6 expression and inhibition of NSCLC progression. These findings suggest that the XIST/miR-329-3p/TMBIM6 axis could serve as a promising molecular target for therapeutic strategies in NSCLC.